Вдосконалення механічних методів вимірювання концентрації паперової пульпи - Романюк, Олександр Миколайович (Національний університет "Львівська політехніка", 2020)
Дисертація присвячена питанням забезпечення інваріантності механічних концентратомірів паперової пульпи до наявних неінформативних параметрів шляхом управління рухом чутливих елементів механічних концентратомірів так, щоб усунути вплив неінформативних параметрів та покращити метрологічні характеристики концентратомірів, що дозволить підвищити точність вимірювання. Запропоновано вимірювати момент сил зсуву, який діє на чутливий елемент ротаційного концентратоміра при його обертанні по черзі на двох попередньо заданих частотах, з повторенням вимірювань при зміні напряму обертання чутливого елемента на зворотний, автоматизовану систему реєстрації та опрацювання результатів вимірювань та систему керування рухом чутливого елемента. Запропоновано спосіб керування лопатковим концентратоміром із активною лопаткою та автоматизовану систему керування рухом лопатки, яка забезпечує сталу швидкість зсуву паперової пульпи. Це дозволяє використати калібрувальні графіки та поправки, які компенсують вплив зміни температури, тиску і типу паперової пульпи ідентичні до використовуваних при роботі ротаційних концентратомірів, та зменшити вплив швидкості течії паперової пульпи на визначене значення її концентрації. Запропоновано алгоритми опрацювання отриманих результатів, які забезпечують зменшення похибок при вимірюванні концентрації паперової пульпи. Диссертация посвящена вопросам обеспечения инвариантности механических концентратомеров бумажной пульпы к существующим неинформативным параметрам путем управления движением чувствительных элементов механических концентратомеров, чтобы устранить влияние неинформативных параметров и улучшить метрологические характеристики концентратомеров, что позволит повысить точность измерения. Предложено измерять момент силы сдвига, действующий на чувствительный элемент ротационного измерителя концентрации при его вращении по очереди на двух предварительно заданных частотах вращения, с последующим повторением изменений при вращении чувствительного элемента в обратном направлении, автоматизированную систему управления вращением чувствительного элемента, и систему регистрации и обработки результатов измерений. Предложены способ управления лопаточным измерителем концентрации с активной лопаткой и автоматизированная система управления движения лопатки, обеспечивающая движение лопатки в потоке бумажной массы с постоянной скоростью сдвига. Это позволяет использовать калибровочные графики и поправки, компенсирующие влияние изменений температуры, давления и типа бумажной массы идентичные используемым при работе ротационных измерителей концентрации, а также уменьшить влияние скорости течения бумажной массы на измеренное значение концентрации бумажной массы. Предложены способы организации процесса измерений и алгоритмы обработки полученных результатов, которые обеспечивают уменьшение погрешностей при определении концентрации бумажной массы. The thesis is devoted to the problem of the enhancement of the paper pulp consistency measurements precision by rotational and active blade-type consistometers. It has been proved that accuracy of the paper pulp consistency measurements in case of rotational consistometer can be increased by measuring of the share stress torque at two predetermined frequencies of the sensitive element rotation, and following repeating of the share stress torque measurements for alternative rotation direction. By averaging of the share stress torque values measured at one frequency of the sensitive element rotation in clockwise and anticlockwise directions, and following algorithmic processing of the obtained data it is possible to eliminate the effect of the asymmetry of the paper pulp flow velocity distribution in the vicinity of consistometer rotating sensitive element. Modern paper pulp rotational consistometers use compensation-measuring method, where the share stress torque is compensated by the torque, produced by electromagnetic transducer, controlled by electric current, or by specially designed electric motor. We proposed to use the magnetoelectric transducer of the share stress torque instead of the electromagnetic transducer because it has a linear relationship between the current and the torque produced. Another important property of the developed magnetoelectric transducer consists in the fact that it can operate at any rotation direction of sensitive element, while available electromagnetic transducers can operate only for one rotation direction and do not support rotation in the opposite one. As information parameter serves the strength of current in the magnetoelectric transducer winding in the moment, when the frequency of the sensitive element rotation come up to one of the two predetermined values f1 or f2 in turn from the side of the lower frequencies and from the side of the higher frequencies. The standard optical mount for the torque compensation monitoring is connected with designed equipment for precision output signal processing providing higher precision and repeatability of the paper pulp consistency measurements. Signals are processed by programmable logic controller Siemens Simatic S7. The method of the active blade control in the paper pulp consistometer, and the automatic control system for supplying blade motion in the paper pulp flow providing constant share rate are presented. The application of the modified (improved) active blade consistometer allows to use the calibration and temperature, pressure, and paper pulp type corrections identical to those used for rotational consistometers, and to reduce the influence of the paper pulp flow velocity on the measured value of paper pulp consistency. The analysis of the factors affecting on the formation of the stored error of the paper pulp consistency measurement by rotational and active blade consistometers is done. The measurement process arrangement and the algorithm of obtained data processing are proposed, providing the reducing of the error of the paper pulp consistency measurement.
Усовершенствование механических методов измерения концентрации бумажной массы
The improvement of the mechanical method of the paper pulp consistency measurements
Keywords: неньютонівські рідини; вимірювання в'язкості; коефіцієнт консистенції; індекс течії; ефективна в'язкість; вимірювання концентрації паперової пульпи; вимірювання в'язкості; ротаційний концентратомір; лопатковий концентратомір; неньютоновские жидкости; измерение вязкости; коэффициент консистенции; коэффициент густоты потока; показатель поведения жидкости; кажущаяся вязкость; измерение концентрации бумажной массы; ротационный измеритель концентрации бумажной массы; лопаточный измеритель концентрации бумажной массы; paper pulp; non-Newtonian liquids; paper pulp consistency measurements; rotational viscometer; rotational consistometer; active blade consistometer; flow consistency index; flow behavior index; apparent viscosity; 532.137